Lifetime measurements of nuclei in few-electron ions. (26th November 2015) - Faestermann, Thomas
Abstract: In this review lifetime measurements of ions with at most two electrons are summarized. Such highly ionized systems have been studied—until now—only in the experimental storage ring of the GSI in Darmstadt. Emphasis is put on decays via the weak interaction. The first observations of beta-decay into bound atomic states are described as well as its time mirrored counterpart, the electron-capture decay. In the latter case the decays of hydrogen- and helium-like ions are compared with a surprising result. Further on, the observation of sinusoidal modulations of the decay rate in two-body decays is summarized. As a possible cause an interference due to the emission of neutrinos with different rest mass is discussed.